Renaissance papers 2016 - Pearce, Jim (Director of Graduate Studies); Risvold, Ward J. (Renaissance papers,, 2017)
Annual volume of the best essays submitted to the Southeastern Renaissance Conference, this year with an emphasis on Shakespeare, reading practices, and the visual arts.